MEASUREMENT OF THE E+E- -] GAMMA-GAMMA(GAMMA) CROSS-SECTION AT LEP ENERGIES - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Almeida, F; Alvsvaag, S; Amaldi, U; et al. (1994)
The total and the differential cross sections for the reaction e+e- → γγ(γ) have been measured with the DELPHI detector at LEP using an integrated luminosity of 36.9 pb-1. The results agree with the QED predictions and consequently there is no evidence for non-standard channels with the same experimental signature. The lower limits obtained on the QED cutoff parameters are Λ+ > 143 GeV and Λ- > 120 GeV, and the lower bound on the mass of an excited electron with an effective coupling constant λγ = 1 is 132 GeV/c2. Upper limits on the branching ratios for the decays Z0 → γγ, Z0 → π0γ, Z0 → ηγ and Z0 → γγγ have been determined to be 5.5 × 10-5, 5.5 × 10-5, 8.0 × 10-5, and 1.7 × 10-5 respectively. All the limits are at the 95% confidence level.